Effect of relief and land use on heat stress in Kraków, Poland - Bokwa, Anita; Limanówka, Danuta (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Heat stress in urban areas is controlled mainly by the impact of anthropogenic land use on the active surface heat balance. This paper shows the role of land form superimposed on the land-use impact, using the example of Krakow, Poland. The city is located in a concave land form, on the Wisla (Vistula) River. The automatic measurements of air temperature and humidity were realised in Kraków from April to October, in the years 2010-2012. For the daytime conditions, ANOVA test and Tukey’s test showed significant differences in the number of very hot days and number of heat waves, between urban areas in the valley and rural areas, both in the valley and on the slope. For the nighttime, significant differences were found for the number of tropical nights, not only between urban and rural areas, but also between urban areas located in various landforms and between urban areas in the valley floor and rural areas located in various landforms. Both urban and rural measurement points located in the river valley floor experienced the highest numbers of very hot days, heat waves and extreme air temperature duration. For measurement points elevated about 50 m above the valley floor, the indices’ values were lower by about 50 %.